Optimizing The Level Of Community Knowledge Regarding The Implementation Of Hospital Triage In Sungai Alat Village, Astambul District - Wardhani, Annalia; Insana Maria (Outline Journal of Community Development, 2024)
Emergency events can occur at any time and anywhere, and require immediate treatment, because they can be life-threatening or cause permanent disability. Emergency incidents can be caused by, among other things, traffic accidents, disease, fire or natural disasters. One of the three main pillars of the Healthy Indonesia Program is strengthening health services, including strategies for increasing access to health services, optimizing the referral system and improving the quality of health services, one of which is through the Integrated Emergency Management System (SPGDT). Providing emergency services has the aim of reducing morbidity and mortality rates so that it requires nurses' ability to classify or sort patients who need help first, which is called triage. Objective: Optimize the level of knowledge regarding the implementation of triage in families so that they can understand the work of health workers in emergency services and avoid complaints to the medical team when receiving services at the hospital. Based on the above phenomenon, the author is interested in conducting community service regarding optimizing the level of knowledge regarding the implementation of Triage for families in Sungai Alat Village, Astambul District. This service activity is in partnership with families in Sungai Alat Village, Astambul District. The activity began with providing material through counseling about hospital triage by distributing leaflets.